(untitled) (MCIT: Proceedings of International scientific and practical conference, 2025)
Обґрунтована доцільність та описаний механізм використання мемоізації для прискорення виконання алгоритму зменшення розміру сформованих DEFLATE-блоків під час прогресуючого ієрархічного стиснення зображень без втрат. На прикладі зображень тестового набору ACT показано, що застосування мемоізації для аналітичного способу реалізації цього алгоритму дає змогу прискорити її виконання максимум на 58.9 %. The feasibility and mechanism of using memoization to accelerate the execution of the algorithm for reducing the size of the formed DEFLATE blocks during progressive hierarchical lossless image compression are substantiated and described. Using the example of images from the ACT test set, it is shown that the use of memoization for the analytical method of implementing this algorithm allows to accelerate its execution by a maximum of 58.9%.